MON-433 The Spectrum Of Growth Hormone Excess In Carney Complex: Characterizing A Common Finding In A Rare Syndrome - Tatsi, Christina (J Endocr Soc, 2019)
Objective: Carney complex (CNC) is a familial lentiginosis and multiple endocrine neoplasia syndrome, caused by PRKAR1A gene mutations in 70% of patients. Involvement of the pituitary somatotrophs may lead to growth hormone (GH) excess; however, little is published about the progress and management of these patients. Objective: To describe the relative frequency of GH excess in a large cohort of patients with CNC, and to identify the characteristics and the natural history of the disorder. Methods: Via retrospective chart review, we identified 135 patients who have been diagnosed with CNC and had at least one clinical and biochemical evaluation of GH secretion at the Clinical Center, NIH, from 1995-2018. GH secretion was considered abnormal if any of the following criteria occurred: elevated IGF1 (according to sex and age- or Tanner-stage reference range), lack of suppression to Oral Glucose Tolerance Test (GH >2ng/mL for samples collected before 1/1/1999, or GH >1ng/mL for samples collected afterwards), increase of GH by > 50% after TRH stimulation test, and mean GH level > 4.5 ng/mL during serial GH sampling. Results: Fifty-five subjects (40.7%) had at least one abnormal result in the diagnostic tests for GH secretion. Twenty-eight subjects (20.7%) had at least 2 abnormal diagnostic tests, and fit the diagnosis of GH excess. The mean age at diagnosis was 26.7 yo (range:5.8-61.2), which was similar with the age at the latest follow up of the remaining patients (p=NS). The presence of PRKAR1A gene mutation was not associated with the presence of GH dysregulation (p= 0.63). Of the patients with dysregulation of GH secretion, 75% had abnormal pituitary MRI at any time of their evaluation: 23.5% before biochemical diagnosis, 41% at the time of the first biochemical finding and 9.8% after biochemical diagnosis. Of the patients with normal GH results, 45% had abnormal findings in the pituitary MRI, including enlargement of the gland or pituitary lesions, which was lower than the GH excess cohort (p=0.001) however clinically significant. Management of the patients differed according to their biochemical findings and clinical symptoms. Of the patients with GH excess and available follow up, 15 patients (55.5%) required more definite treatment: 7/15 were treated with somatostatin analogues and 8/15 underwent transsphenoidal resection of a pituitary adenoma, while the remaining retained mild GH excess despite no intervention. Conclusion: Dysregulation of GH secretion is a common finding in CNC. The spectrum of the disorder ranges from isolated structural abnormalities identified at imaging studies, mild dysregulation of growth hormone secretion, and clinically significant GH excess. The diagnosis of growth hormone excess and the selection of patients requiring any intervention is of outmost importance given the potential implication of GH excess in tumor progression and subsequent comorbidities.